SIFAT-SIFAT DASAR PERLUASAN INTEGRAL LEBESGUE - Lesnussa, Yopi A.; Wattimanela, Henry J.; Talakua, Mozart W. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
EL-Integral is extended of Lebesgue integral, 1 k b EL f d L f d . Lebesgue integral is defined with early arrange measure theory that famous with Lebesgue measure. A function f :ï›a,bïï‚®ïƒ‚ is said EL-integrable on ï›a,bï , if there exist series interval that no piled up ï» ï½ k I in ï›a,bï so that ï€¨ï› , ï ï€© 0 k ï a b ï€ I ï€½ , ï€¨ ï€© k f ïƒŽL I for every k and 1 IkA L f dï finite. Value A is called value of EL Integral function f on ï›a,bï . Extended of Lebesgue integral (EL-Integral) is notated by : ï€¨ kbE a k I EL f dï f dï L f dïï‚¥ï€½ïƒ² ï€½ ïƒ² ï€½ïƒ¥ ïƒ² .